Prospective identification of glioblastoma cells generating dormant tumors - Satchi-Fainaro, Ronit; Abdollahi, Amir; Almog, Nava (PLOS ONE, 2012)
Although dormant tumors are highly prevalent within the human population, the underlying mechanisms are still mostly unknown. We have previously identified the consensus gene expression pattern of dormant tumors. Here, we show that this gene expression signature could be used for the isolation and identification of clones which generate dormant tumors. We established single cell-derived clones from the aggressive tumor-generating U-87 MG human glioblastoma cell line. Based only on the expression pattern of genes which were previously shown to be associated with tumor dormancy, we identified clones which generate dormant tumors. We show that very high expression levels of thrombospondin and high expression levels of angiomotin and insulin-like growth factor binding protein 5 (IGFBP5), together with low levels of endothelial specific marker (ESM) 1 and epithelial growth factor receptor (EGFR) characterize the clone which generates dormant U-87 MG derived glioblastomas. These tumors remained indolent both in subcutaneous and orthotopic intracranial sites, in spite of a high prevalence of proliferating cells. We further show that tumor cells which form U-87 MG derived dormant tumors have an impaired angiogenesis potential both in vitro and in vivo and have a slower invasion capacity. This work demonstrates that fast-growing tumors contain tumor cells that when isolated will form dormant tumors and serves as a proof-of-concept for the use of transcriptome profiles in the identification of such cells. Isolating the tumor cells that form dormant tumors will facilitate understanding of the underlying mechanisms of dormant micro-metastases, late recurrence, and changes in rate of tumor progression.